The sustainable nation : politics, economy and justice - Leonard, Liam (Emerald Publishing Limited, 2017)
Drawing on almost 20 years of Liam Leonard's research in the field, this volume provides a detailed case study of a modern European state's tumultuous development through first decades of the Millennium. The book provides an in depth and up to date study on Ireland's growth and the substantial changes experienced there during the last two decades.
Keywords: Economic development -- Ireland.; Sustainable development -- Ireland.; Environmental justice -- Ireland.; Ireland.; elektronické knihy; electronic books